Prioritization of natural extracts by LCMS-PCA in identification of new photosensitizers for photodynamic therapy - Samat, Norazwana (2015)
Photodynamic therapy (PDT) is an alternative treatment for cancer that involves administration of a photosensitive drug or photosensitizer that localizes at the tumour tissue followed by in situ excitation at an appropriate wavelength of light. Tumour tissues are then killed by cytotoxic reactive oxygen species generated by the photosensitizer. Targeted excitation and photo-killing of affected tissues is achieved through focal light irradiation, thereby minimizing systemic side effects to the normal healthy tissues. Currently, there are only a small number of photosensitizers that are in the clinic and many of these share the same structural core based on cyclic tetrapyrroles. This study describes how metabolomic tools are utilized to prioritise natural extracts to search for structurally new photosensitizers from Malaysian biodiversity. As proof of concept, 278 photocytotoxic extracts has been analyzed using a hyphenated technique of liquid chromatography mass spectrometry coupled with principal component analysis (LCMS-PCA) and 27 extracts that potentially contained new photosensitizers were prioritized for chemical dereplication using an in-house UPLC-PDA-MS-Photocytotoxic assay platform. This has led to the identification of 2 new photosensitizers with cyclic tetrapyrrolic structures, thereby demonstrating the feasibility of the metabolomic approach.